‘Oh, there are so many things I want to write’ : Becoming an author: Doris Lessing and the Whitehorn Letters from 1944 to 1949 - García Navarro, Carmen (International Journal of English Studies, 2019)
This paper explores the narrative process identified in the Whitehorn Letters, written by Doris Lessing from 1944 to 1949, as historical documents that form a single, coherent whole. Their significance is assessed by means of an epistemological reflection that sheds light on the path by which the young Lessing established her identity as an author (Bieder, 1993). In the letter-writing process, Lessing declares her aim to become a writer. The letters also characterise the writer as a historical subject, and describe the relationship between this historical subject and the individual who writes the correspondence. Since the letters formulate a coherent discourse about Lessing’s authorial identity, I investigate whether using a model for reading them may be beneficial. I believe that additional nuances could be detected in her narratives by revisiting Lessing and examining, in the centenary of her birth, some hitherto unknown parts of her writings, as these letters represent.